Anti-hyperlycemic and hypolipidemic effect of oral administration of Capsicum frutescens in male STZ-diabetic rats - M Roghani; T Baluchnejadmojarad; Z Sohrabi; M Sadeghi (Institue of Medicinal Plants, ACECR, 2004)
There are few reports on the antidiabetic effect of the medicinal plant red pepper. Since there is no strong documentation for its efficacy in diabetic state, therefore, its hypoglycemic and hypolipidemic effect was investigated in an experimental model of insulin-dependent diabetes mellitus. For this purpose, male Wistar rats (n = 36) were randomly divided into 4 groups, i.e. control, pepper-treated control, diabetic, and pepper-treated diabetic groups. For induction of diabetes, streptozotocin (STZ 60 mg/Kg i.p.) was used at a single dose. A serum glucose level higher than 250 mg/dl was considered as the presence of diabetic state. The treatment groups received oral administration of pepper-mixed pelleted food at a ratio of 1/15. Statistical analysis of the data showed that serum glucose level in diabetic group increases 2 and 4 weeks after the experiment as compared to data one week before the experiment (p<0.001), while this parameter was only significantly lower 2 weeks after the experiment in pepper-treated diabetic group as compared to untreated-diabetic group (p<0.01). In addition, there was no significant difference between pepper-treated control and untreated control groups regardiong serum glucose level. In addition, triglyceride level was higher in diabetic group and there was a reduction in this parameter in pepper-treated diabetic group as compared to diabetic group at fourth week after the experiment (p<0.05). On the other hand, cholesterol level showed no significant reduction in pepper-treated diabtic group in comparison with untreated diabetic group. Taken together, the results of this study clearly showed that oral administration of red pepper in short-term could significantly reduce serum glucose level and in long-term could only reduce triglyceride level in diabetic rats. Therefore, this medicinal plant is recommended for attenuation of some diabetic complications due to hyperglycemia and hyperlipidemia.